TGF-β2 Regulates Transcription of the K+/Cl− Cotransporter 2 (KCC2) in Immature Neurons and Its Phosphorylation at T1007 in Differentiated Neurons - Anastasia Rigkou; Attila Magyar; Jan Manuel Speer; Eleni Roussa (Cells, 2022)
KCC2 mediates extrusion of K+ and Cl− and assuresthe developmental “switch” in GABA function during neuronal maturation. However, the molecular mechanisms underlying KCC2 regulation are not fully elucidated. We investigated the impact of transforming growth factor beta 2 (TGF-β2) on KCC2 during neuronal maturation using quantitative RT-PCR, immunoblotting, immunofluorescence and chromatin immunoprecipitation in primary mouse hippocampal neurons and brain tissue from Tgf-β2-deficient mice. Inhibition of TGF-β/activin signaling downregulates Kcc2 transcript in immature neurons. In the forebrain of Tgf-β2−/− mice, expression of Kcc2, transcription factor Ap2β and KCC2 protein is downregulated. AP2β binds to Kcc2 promoter, a binding absent in Tgf-β2−/−. In hindbrain/brainstem tissue of Tgf-β2−/− mice, KCC2 phosphorylation at T1007 is increased and approximately half of pre-Bötzinger-complex neurons lack membrane KCC2 phenotypes rescued through exogenous TGF-β2. These results demonstrate that TGF-β2 regulates KCC2 transcription in immature neurons, possibly acting upstream of AP2β, and contributes to the developmental dephosphorylation of KCC2 at T1007. The present work suggests multiple and divergent roles for TGF-β2 on KCC2 during neuronal maturation and provides novel mechanistic insights for TGF-β2-mediated regulation of KCC2 gene expression, posttranslational modification and surface expression. We propose TGF-β2 as a major regulator of KCC2 with putative implications for pathophysiological conditions.